ANALYSIS OF THE EFFECT OF BX 92, BX ULTIMAXX FUEL AND THEIR MIXTURES ON THE PERFORMANCE OF THE R15 MOTORCYCLE - Afif , Muhammad Syauqi; Firdaus , Rachmat (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: With the rapid advancement of automotive technology, especially motorbikes, fuel performance has become increasingly crucial in optimizing vehicle efficiency and meeting the demands of rising motorbike usage. Specific Background: Among commonly used fuels like BX 92 and BX Ultimaxx, the performance of different fuel types and combinations on power, torque, and specific fuel consumption (SFC) remains underexplored. Knowledge Gap: While various fuels are utilized, a detailed comparative analysis of motorbike performance using different fuels and blends, including ethanol mixes, is limited, particularly in the context of octane levels and engine power. Aims: This study aims to analyze motorbike performance differences when using BX 92, BX Ultimaxx, a 50:50 blend of BX 92 and BX Ultimaxx, and an 85:15 blend of BX 92 and ethanol, assessing power, torque, and SFC on an R15 motorbike using dynotest equipment. Results: The study found that higher octane levels yield improved power and torque, with BX Ultimaxx performing best in terms of power but consuming more fuel. BX 92 proved most efficient in fuel consumption but ranked lower in performance compared to BX Ultimaxx. The BX 92-BX Ultimaxx blend showed moderate improvements in power over BX 92 alone, while the BX 92-ethanol blend exhibited the lowest performance of all fuels tested. Novelty: This study provides a novel comparative framework for evaluating mixed fuel impacts on motorbike performance, particularly in utilizing ethanol as an alternative fuel component. Implications: These findings suggest that while higher-octane fuels enhance performance, fuel blending strategies could be optimized for specific outcomes, balancing efficiency with performance, thereby contributing to more sustainable fuel use in the automotive industry.